Patronage, Power, and Livelihood Dispossession: A Political Ecology of Coal Extraction in East Kalimantan - Monalisa, Monalisa; Murlianti, Sri; Makmur, Harun; Ali, Abdul Halim (Universitas Negeri Semarang, 2025)
East Kalimantan’s rural frontier has become a key arena of Indonesia’s dual extractive economy, where coal mining and oil-palm plantations intersect to reshape village life. In Long Beleh Modang Village, overlapping concessions, uncontrolled land clearing, and weak state regulation have produced a “common problem” of ecological degradation and livelihood precarity: forests are fragmented, rivers polluted, and customary tenure eroded. Communities that once relied on forest and river resources face declining access to natural capital, deepening economic dualism, and growing dependence on informal patronage networks. Against this background, this article investigates how the combined expansion of coal and oil-palm industries transforms rural livelihood structures and reconfigures local power relations. Using a qualitative case-study design—comprising in-depth observation, semi-structured interviews, and focus group discussions—the study applies the Sustainable Livelihoods Analysis (SLA) framework not as a full livelihood assessment, but specifically to explain how extractivism drives structural inequality and erodes community livelihood capitals (natural, physical, human, social, and financial). Political-ecology concepts complement this analysis to reveal the power dynamics behind dispossession. The findings show a shift from adaptive to coping strategies, marked by land fragmentation, heightened informal labor, and declining access to natural resources. Agrarian conflict is intensified by overlapping tenure claims and the absence of participatory land governance. An emergent system of extractive patronage, where local elites broker access to corporate resources, reinforces economic inequality and social exclusion. By demonstrating how SLA illuminates the structural erosion of livelihood assets under extractive pressure, this study contributes to debates on extractive governance and rural sustainability, underscoring the urgency of equity-oriented, community-based governance and participatory spatial planning.